Perceptions of safety among visitors to China: feeling safe in an unfamiliar environment. Issue 1 (10th December 2020) - Zou, Yongguang; Mawby, Rob I.
Abstract : Purpose: The purpose of this paper is to address four questions: Firstly, how do tourists perceive safety from crime, specifically from robbery or violence, alongside other safety concerns? Secondly, are those who are concerned about crime also concerned about other threats to their well-being? Thirdly, how are their perceptions of safety affected by their perceptions of the local community? Finally, how are their perceptions affected by their personal and touristic characteristics? Design/methodology/approach: Findings: Firstly, tourists did not generally see crime, specifically robbery or violence, as a problem; secondly, there was only a weak relationship between concern about crime and concern about other threats to their well-being; thirdly, in contrast, their perceptions of safety were strongly affected by their perceptions of the local community; and finally, their perceptions were affected by their personal and touristic characteristics, but not necessarily in the ways suggested by earlier research. Research limitations/implications: The research sample was small and the questionnaire short. Only English-speaking visitors were included. Practical implications: The tourism sector needs to appreciate role of local people in engendering feelings of safety. Social implications: The attitude of the local community and their relationship with tourists is fundamental to helping visitors feel safe. Originality/value: This is the first criminological paper to compare fear of crime with the other safety issues confronting tourists and to relate these concerns to relationships with host community.